The Influence of Product Quality and Price on Costumer Satisfaction at Warkop Simple in Sumedang - Hidayat, Gustina; Gumilang, Gilang; Nadhirah, Lulu Tasya; Putri, Meidah Cahaya; Saefuloh, Muhammad (Journal of Bussines Management Basic, 2025)
This research aims to analyze the influence of product quality and price on customer satisfaction at Warkop Simple in Sumedang. The study uses a quantitative approach by distributing questionnaires to 96 respondents, with samples collected using accidental sampling techniques. The independent variables in this study are product quality and price, while the dependent variable is customer satisfaction. The results of multiple linear analysis show that both product quality and price have a significant effect on customer satisfaction, both partially and simultaneously. The coefficient of determination (Adjusted R2) of 76.4% indicates that the variables of quality and price explain most of the variation in customer satisfaction, while the remaining 23.6% is influenced by other factors not covered in this study. The study concludes that product quality and price are important factors in increasing customer satisfaction at Warkop Simple. The recommendations provided include maintaining consistent product quality, enhancing menu innovation, and developing competitive pricing strategies to sustain competitiveness in the local.